Undercover baby rescue - Black, Maggie K. (Love inspired suspense., 2023)
"A dangerous organization is kidnapping and trafficking newborns--and Officer Justin Leacock's nephew is their latest victim. To save the stolen baby, Justin will have to go undercover as a married couple with his former fiancée, Detective Violet Jones. Except finding the boy isn't enough. Now they must outwit the kidnappers on their tail and survive the ruthless icy wilderness, too..."--Page 4 of cover.